AISprayAndWait: An AI-Enhanced Routing Protocol for Delay Tolerant Networks - Halikul, Lenando; Sanjay Charles, Albert; Inson, Din; Chon Eng, Tan (2025)
Delay Tolerant Networks (DTNs) operate in intermittent network connectivity and dynamic topology. This poses a challenge to achieving efficient data ex-change. Traditional routing protocols such as Epidemic, Spray and Wait, and PRoPHET aim for high delivery but suffer from high overhead. This paper intro-duces AISprayAndWait, a lightweight AI-enhanced routing protocol that builds upon the Spray and Wait mechanism by integrating intelligent forwarding deci-sions. The protocol evaluates four contextual features—encounter frequency, re-cency of contact, buffer availability, and a bias term—to compute a forwarding score using a sigmoid function. The simulation results demonstrate that AISprayAndWait significantly improves delivery probability and reduces over-head compared to existing protocols. These findings show that lightweight AI in-tegration is possible in optimizing DTN routing strategies.